Beyond narrative: Is there an implicit structure to the way in which adults organise their discourse? - Whitworth, Anne; Claessen, Mary; Leitão, Suze; Webster, J. (Informa Healthcare, 2015)
Understanding the structure of discourse in healthy adults is fundamental to the assessment and diagnosis of discourse level impairments in clinical populations and the development of effective treatment regimes. Exploring discourse genre in healthy speakers that extend beyond the traditional narrative is equally paramount in facilitating maximum impact of clinical interventions in everyday speaking contexts. This study aimed to characterise the discourse of 30 healthy adult speakers across three age groups (20–39, 40–59 and 60+ years) and four discourse genres (recount, procedural, exposition and narrative), drawing on discourse frameworks used in classroom teaching. A clinically useful discourse protocol and analytic procedure using SALT was developed that profiled the macrostructure and key aspects of linguistic microstructure of the different genres, exploring coherence and cohesion within and across genre in a systematic manner. Analyses considered whether there were differences in coherence and cohesion among the different age groups, different genres and specific topics. Results showed that, while individual variability was present, healthy adults structured their discourse consistently, adhering to the frameworks described in the developmental literature, across all four genres. Significant age differences were only seen in the amount of information contained in the body of the discourse (i.e. events, steps or statements offered) with older participants offering less information. This dataset will enable comparisons to be drawn with clinical populations to determine the utility and the feasibility of the use of this framework for diagnosis and intervention.